A Study to Evaluate the Effectiveness of Health-Care Package on Self-care Management and Prevention of Complications in Patients with Type-2 Diabetes Mellitus in Terms of the Knowledge and Practices in Diabetic Clinic of Selected Hospitals in Delhi - Veer Kharol, Dharm; Kharol, Mahendra (International Journal of Nursing Research, 2023)
Introduction: The aim of this study were to prevent, control, and manage diabetes mellitus (DM) and its further consequences, it is essentially required that the diabetic patients should have adequate knowledge and adopt healthy lifestyle practices. Objectives: The objectives of this study were to evaluate the effectiveness of the health-care package on self-care management and prevention of complications in type 2 DM patients in terms of the knowledge and practices. Materials and Methods: The present study was conducted with evaluative research approach and non-randomized control group design at Safadarjung Hospital, Delhi. Sample was selected through non-probability purposive sampling technique and sample size consisted of 60. The tools for data collection included structured interview schedule and expressed practice questionnaire. The health-care package included – planned teaching program, self-care diary cum information booklet, diabetic identification card, diet chart, and pictorial/flash cards. Results: There was a significant “t” value of 15.882, df (29), P < 0.05 and “t” value of 9.86, df (29), P < 0.05 for mean pre- and post-test, knowledge and practice scores of experimental group and, significant “t” value of 9.1, df (58), P < 0.05 and “t” value of 11.45, df (58), P < 0.05 for mean post-test, and knowledge and practice scores of experimental and control group. There was also found a positive correlation r = 0.948, P < 0.05 between post-test knowledge and practice scores of experimental group. Study findings also conclude significant association of post-test, knowledge scores with educational level (χ² = 16.533*, df=6, P < 0.05), per capita income (χ² = 10.093*, df=3, P < 0.05), practice scores with educational level (χ² = 17.2*, df=6, P < 0.05), and per capita income (χ² = 8.422*, df=3, P < 0.05) of type 2 diabetic patients. Conclusion: The study findings revealed that health-care package was found to be effective in enhancing the knowledge and improving the practices of the type 2 diabetic patients.